FAKTOR-FAKTOR EKONOMI YANG MEMPENGARUHI FLUKTUASI NILAI TUKAR DOLLAR AMERIKA SERIKAT TERHADAP RUPIAH DI BANK INDONESIA - Sri Prilmayanti Awaluddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
Inflation can be said to have a major influence on the exchange rate fluctuations. If the inflation rate in Indonesia increased substantially while the rate of inflation in the United States is relatively fixed it will make the price of products in Indonesia is becoming increasingly expensive. The purpose of this paper is to identify and analyze which of the variables of inflation, exports and imports, and interest rates are the most dominant influence fluctuations in the US dollar against the rupiah in Indonesia. Data obtained from research literature (library research) and the Research field (field research. The analytical method to be used is as follows: Multiple regression analysis, coefficient of determination (R2), Unison Significance Test (Test F) and Individual Significance test (t test). The results showed that all three variables simultaneously research is the inflation rate, 1-month SBI interest rate, and the value of exports and imports significantly affect the magnitude of the increase in the exchange rate against the US dollar. Then the third partial test of these variables to changes in the exchange rate against the US dollar, then you see the three variables that did not show any significant effect. although the three variables does not indicate that the significance of the effect on the rupiah against the US dollar, but if compared to the three variables, then the inflation rate further demonstrate its impact on the rupiah against the US dollar. sequentially, 0.2209, and -0.243, and using a significance level of 5%, the obtained value of 1,706 t-table. Large t-test for the inflation rate is thus showing -0.3611 -0.3611 <-1.706 with a probability level of 0.721> 0.05, it can be explained that the inflation rate does not significantly influence fluctuations in the exchange rate of the US dollar against the rupiah. For SBI rate 1 month acquired by t-test 0.2209 <1.706 with a probability level of 0.8270> 0.05 also shows that the rate of 1-month SBI rate showed no significant effect on the fluctuations in the exchange rate of the US dollar against the rupiah. T-count value to the value of exports and imports amounted to -0.2430 <-1.706 to 0.8100 probabiliti levels> 0.05 indicates that the value of exports and imports do not give a significant influence on the exchange rate of the US dollar against the rupiah in Indonesia.